Full-scale simulator to test a control system of an engine-propeller powerplant of a convertible aerial vehicle - D. V. Vereshchikov; I. K. Makarov; I. S. Moiseeva; S. M. Barantsev (Научный вестник МГТУ ГА)
The article presents the results of work involved with developing a full-scale simulator for research into determining the structure and parameters of the control system for unmanned aerial copter-type vehicles with a powerplant comprising electric motors with fixed-pitch propellers. The features of the engineering implementation of the simulator, taking into account the prospects for its development in terms of greater maneuverability (pitch, roll and yaw), are presented. The implemented principle of the Simulink integration – a model of the control object, a controller based on the Arduino platform, a gyroscope-accelerometer to organize feedbacks for the purpose of forming algorithms of the automatic and positional (manual) pitch angle control, manual motor revs control is described. The analysis of the full-scale simulation results in terms of the quality of transients and power costs for various settings of the PID-regulator, which provides generating a signal of electric motor revolutions, is presented. It is concluded that it is feasible to create and use an experimental base to justify the use of adaptive control algorithms for unmanned aerial copter-type vehicles with elements of artificial intelligence to ensure the required flying characteristics in a wide range of properties of control objects.